Johann Sebastian Bach. Ein verplichtendes Erbe - Hindemith, Paul 1895-1963 (Wiesbaden Insel, 1958)
Hindemith argues that Johann Sebastian Bach's music represents an essential foundation for Western classical music. He emphasizes that Bach’s works are not just important historically but must be studied and understood as a standard for any serious musician. The essay advocates that Bach's music is not only a model for technical mastery but also for compositional depth, beyond sound (and historically informed performance). Hindemith believed that Bach's music embodied a perfect blend of counterpoint, harmonic structure, and intellectual rigor, making it a key to understanding the evolution of Western music. He suggests that musicians and composers of his own time, and in the future, should view Bach’s music as an indispensable part of their education and creative process. Hindemith's take on Bach is deeply rooted in the German tradition of reverence for Bach's genius.
Lecture given at the Bachfest, Hamburg, 12 September 1950
Ex libris Eva Dellmann, 1960 (manuscript). Contains a postcard with a dedication from Eva Dellmann to Albert Dunning
Keywords: Bach, Johann Sebastian -- 1685-1750; 18th Century (1701-1800); 20th Century (1901-2000); Composer; Legacy; Germany